2019
DOI: 10.12965/jer.1938060.030
|View full text |Cite
|
Sign up to set email alerts
|

Low intensity training improves redox status and reduces collagen fibers on dystrophic muscle

Abstract: Exercise therapy on skeletal muscle of muscular dystrophies has no defined parameters. The effect of low-intensity treadmill training on the oxidative stress markers and fibrosis on hindlimb muscles was investigated. Sixteen dystrophic male mdx animals were separated in trained ( mdx T/n=8) and untrained ( mdx NT/n=8) groups. Wild type animals (WT/n=8) were used as healthy control. The mdx T group runned at a horizontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
(58 reference statements)
0
6
0
3
Order By: Relevance
“…In fact, a voluntary swimming training for 30 min, 4 days/week for 4 weeks, improved the expression of proteins involved in energy metabolism and in muscle contraction, as well as decreased oxidized proteins (Hyzewicz et al, 2015). Low-intensity treadmill training (9 m/min, 30 min/day, three times/week, for 8 weeks) reduced collagen deposition, enhancing both enzymatic and total antioxidant capacity (Fernandes et al, 2019).…”
Section: Exercise-related Oxidative Stress In Dmd Animal Modelsmentioning
confidence: 97%
“…In fact, a voluntary swimming training for 30 min, 4 days/week for 4 weeks, improved the expression of proteins involved in energy metabolism and in muscle contraction, as well as decreased oxidized proteins (Hyzewicz et al, 2015). Low-intensity treadmill training (9 m/min, 30 min/day, three times/week, for 8 weeks) reduced collagen deposition, enhancing both enzymatic and total antioxidant capacity (Fernandes et al, 2019).…”
Section: Exercise-related Oxidative Stress In Dmd Animal Modelsmentioning
confidence: 97%
“…Several studies have shown that treadmill exercise can efficiently modulate this process. Indeed, a low intensity exercise, at a speed of 9 m/min for two months, on a horizontal platform reduces collagen deposition in limb muscles of mdx mice [ 73 , 74 , 75 ]. In addition, low intensity running induced a strong beneficial effect on the degeneration-regeneration process of mdx muscle and a shift in favor of regeneration, both in limb muscles and in diaphragm [ 76 , 77 ], and reduced the percentage of necrotic area in mdx soleus and gastrocnemius muscles, while it seemed to exert opposite effects on mdx plantaris muscle [ 78 ].…”
Section: Effects Of Exercise On Plastic Remodeling Of MDX Musclementioning
confidence: 99%
“…Based on the above reported experimental evidences, we can conclude that beneficial effects on mdx limb muscles induced by horizontal treadmill running exercise depend primarily on training intensity, being mainly associated to running speed ranging between 4 and 9 m/min. These positive effects, including fibrosis reduction, increased regeneration, improvement of muscle performances and structure, such as muscle hypertrophy and fiber type switch, seem to be not influenced by age, since they can be found in mdx mice 4–5 weeks old [ 108 , 109 ], 8 weeks old [ 74 , 76 , 77 , 110 ], and up to 20 weeks old [ 73 , 75 , 79 ], or by the duration of training, given the persistence of positive effects for exercise duration ranging between 1 and 6 months. On the contrary, horizontal treadmill exercise at higher intensity, with speed equal or greater than 12 m/min, or downhill/uphill running, generally exert detrimental effects on mdx muscles, and are often used to worsen the mdx phenotype before assessing the efficacy of drug treatment [ 8 , 81 , 82 , 84 , 87 , 92 , 99 ].…”
Section: Effects Of Exercise On Plastic Remodeling Of MDX Musclementioning
confidence: 99%
See 2 more Smart Citations